PENGEMBANGAN AUGMENTED REALITY PADA PEMBELAJARAN GEOMETRI DI KELAS V SEKOAH DASAR - Tasya Alinda; Jessy Alexander Alim; Muhammad Fendrik (STKIP Subang, 2025)
This study aims to develop a valid and practical Augmented Reality (AR)-basedlearning media for teaching geometry in fifth-grade elementary school. Theresearch employs a Research and Development (R&D) approach using the ADDIEmodel, which consists of five stages: Analysis, Design, Development,Implementation, and Evaluation. Data were collected through interviews andquestionnaires, then analyzed using quantitative and qualitative methods. Thevalidation results show an Aiken’s V validity index of 0.94, indicating a very highlevel of validity. A one-to-one trial revealed that the media functioned effectivelywithout significant issues and received positive feedback from students.Practicality was assessed through teacher and student questionnaires, withaverage scores of 97.5% and 97.87%, respectively, both categorized as verypractical. The feedback from both teachers and students was overwhelminglypositive. Therefore, the developed AR learning media is considered valid andpractical, making it suitable for use in teaching geometry to fifth-grade elementaryschool students.